A test method to evaluate the fuel oil corrosion resistance of asphalt binders. (19th July 2021) - Du, Xiaobo; Liu, Shaohui; Zhang, Hongchao; Liu, Wenchang; Lin, Hongwei
Highlights: The BBS test was modified to evaluate the fuel oil corrosion resistance of asphalt. Appropriate experimental parameters are recommended for this test. The cohesive strength loss of asphalt binders due to oil immersion was measured. This test is of simple operation, high accuracy, and good discrimination. Abstract: The oil immersion binder bond strength (BBS) test, a test method based on the well-established BBS test, was designed and performed. This method evaluates the fuel oil corrosion resistance performance of asphalt binders indirectly according to the loss of pull-off tensile strength (POTS) due to fuel oil corrosion, defined as ΔPOTSO values. First the effects of loading rate and asphalt film thickness on the oil immersion BBS test results were studied. Oil immersion BBS tests under various conditions were then applied in order to study the changes in POTS and ΔPOTSO values with oil immersion duration and oil temperature. Suitable experimental conditions were determined in these two steps. Finally, oil immersion BBS test findings were analyzed in comparison with those of other performance tests. Results indicate the selection of 0.7 MPa/s and 0.2 mm as the appropriate loading rate and asphalt film thickness, respectively. Various oil immersion durations and oil temperatures had different impacts on the POTS and ΔPOTSO values of different asphalt binders, with ΔPOTSO values indicating the cohesive strength loss of asphalt binders due to oil immersion. Increases in the ΔPOTSO values of these asphalt binders gradually lessened with increasing oil immersion duration. Furthermore, the ΔPOTSO values of most asphalt binders were related to their solubility in diesel oil, according to asphalt fuel oil corrosion tests. ΔPOTSO values obtained under the conditions of 40 °C for 2 h were positively correlated with results of asphalt mixture performance tests, thus determining the appropriate oil temperature and oil immersion duration for the oil immersion BBS test. Under appropriate conditions, the oil immersion BBS test has the advantages of simple operation, high accuracy, and good discrimination.